Full cost of diagnostic pathology for lung carcinoma in Italy: results from four Pathology Units - Lazzaro, Carlo; Fattore, Giovanni; Barberis, Massimo; Buttitta, Fiamma; Cassoni , Paola; Graziano, Paolo; Marchetti, Antonio; Crema, Stefania; Dal Pero, Francesca; Papotti, Mauro Giulio (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2023)
Objective. To calculate the full cost of diagnostic pathology tests for Non-Small Cell Lung Cancer (NSCLC) across four Italian Pathology Units. Methods. Pathology Units were located in private (2) and public (2) hospitals distributed across the Italian territory (North: 2; Centre: 1; South: 1). Pathologists provided via questionnaire data on tests on NSCLC samples along with the identification and quantification of the necessary healthcare resources (diagnostic technologies, laboratory instruments and personnel). Resources were valued according to hospital-specific unit, yearly and hourly costs (disposables; technologies; professional clusters). Results. The full cost per NSCLC tissue sample included histopathological immunophenotypic and required molecular analysis. Overall, it reached € 659.77 and it was mainly composed of direct costs (77.69%). The processing of a NSCLC tissue sample was labour intensive, as a relevant share of the full cost (44.98%) was actually due to personnel costs, with laboratory technicians, biologists and pathologist driving this finding (17.09%,12.43% and 10.81%, respectively). Conclusions. The results of this research can facilitate the negotiation of new dedicated tariffs for NSCLC sample processing with the national or local third party-payers.